Design Of Online Arabic Language Learning Based On Independent Learning In Islamic Banking Study Program STEBANK Islam - Khambali, Khambali; Machmudah, Umi; Halimi, Halimi (Ijaz Arabi Journal of Arabic Learning, 2024)
Islamic Banking Study Program STEBANK Islam Mr. Sjafruddin Prawiranegara is a private Islamic religious higher education institution with two credits in Arabic language learning as one of the instruments used to achieve a graduate profile. The learning achievement target with the weight given is very minimal; therefore, in order for Arabic language learning to be effective and efficient, independent learning needs to be designed which is supported by an online system that provides learning freedom; this is as recommended by the Ministry of Education and the Ministry of Religion. This descriptive qualitative research describes the design of online Arabic language learning based on independent learning in the Sharia Banking study program at STEBANK Islam Mr. Sjafruddin Prawiranegara. The results show that although independent learning tends to be directed at skill mastery in non-formal education, the principles can be applied to formal education by providing limits in the form of competency mastery targets with a time duration determined by the institution that learners must adhere to with a learning system that provides flexibility in time and place.